PENGEMBANGAN PENDIDIKAN KARAKTER DALAM MATA KULIAH EVALUASI PEMBELAJARAN MELALUI PENDEKATAN DEEP APPROACH TO LEARNING - Suryani, Nanik; Pramushinto, Hengky (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The objectives of this study are to find and to test the model of characters education in Learning Evaluation Subject through deep approach to learning. The subject of the study is the class of Learning Evaluation of Office Administration Program, Economics Education Department, Economics Faculty, Semarang State University. The data are collected by a test, and then analyzed by qualitative descriptive. The result of this study showed that the model of characters education through deep approach to learning could improve studentsâ self awareness in learning the subject.